2006
DOI: 10.1002/jcp.20676
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ‐regulated tight junction development during human urothelial cytodifferentiation

Abstract: Urothelial barrier function is maintained by apical membrane plaques and intercellular tight junctions (TJ). Little is known about the composition and regulation of TJ expression in human urothelium. In this study, we have characterised the expression of TJ components in situ and their regulation in an in vitro model of differentiating normal human urothelial (NHU) cells. In normal ureteric urothelium in situ, there was a differentiation-associated profile of claudins 3, 4, 5, 7, ZO1 and occludin proteins. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 29 publications
8
89
0
2
Order By: Relevance
“…There was no effect on claudin 1 protein expression, which has previously been shown not to be affected by PPARg activation. 9 NHU cells treated with IRF-1 siRNA inhibited the TZ and PD153035-mediated induction of IRF-1 protein expression by 60% (Figure 5b). The induction of FOXA1 protein by combined treatment with TZ and PD153035 was inhibited by 40%, by siRNA to FOXA1 (Figure 5b).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…There was no effect on claudin 1 protein expression, which has previously been shown not to be affected by PPARg activation. 9 NHU cells treated with IRF-1 siRNA inhibited the TZ and PD153035-mediated induction of IRF-1 protein expression by 60% (Figure 5b). The induction of FOXA1 protein by combined treatment with TZ and PD153035 was inhibited by 40%, by siRNA to FOXA1 (Figure 5b).…”
Section: Resultsmentioning
confidence: 94%
“…6,7 Urothelium is the transitional epithelium that lines the luminal surface of the bladder and associated urinary tract, where it functions primarily as a urinary barrier. The urothelium is comprised of basal, intermediate and superficial cell zones, which may be distinguished on the basis of differential cytokeratin (CK) 8 and claudin 9 isotype expression profiles and by the expression of urothelium-specific uroplakins (UPK) by the superficial cells. 10,11 Whereas claudins are components of the intercellular tight junctions that determine paracellular barrier function, the uroplakins interact to form characteristic asymmetric unit membrane (AUM) plaques in the superficial apical membrane, which contribute to transcellular barrier function.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data endorsed previous observations,39, 40, 41 and supported an UPEC infection mechanism involving manipulation of the paracellular pathway. Tight junction investigation in primary urothelial cells has shown that claudin 3, ZO‐1 and ZO‐1α + are important for the correct functionality of tight junctions in urothelia,42, 43 with the loss of ZO‐1 associated with UPEC infection of bladder epithelia39 and a potential UPEC target.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial cells were induced to differentiate by co-activation of PPARγ and inhibition of EGFR signalling as described [12,20,21]. RNA was isolated, cDNA synthesised and realtime PCR performed using TaqMan™ PCR primers with UPK2, UPK3a and GAPDH probes [22].…”
Section: Urothelial Cytodifferentiationmentioning
confidence: 99%